Territorialité et territoires de chasse familiaux chez les Atikamekw Nehirowisiwok dans le contexte contemporain - Éthier, Benoit; Poirier, Sylvie (Anthropologica, 2018)
This article analyses land tenure and resource management patterns of the Atikamekw Nehirowisiwok (Upper-Mauricie, Quebec), as well as the forms of authority and responsibility carried out within family territories. The concepts of “indigenous territorialities” and “relational ontology” allow us to better understand the nature and content of the Atikamekw Nehirowisiwok’s relationships with their forest world and the non-humans; that of “entangled territorialities” refers to the modalities of coexistence between indigenous people and non-indigenous. In order to explain the complexity and dynamics of nehirowisiw territoriality, this analysis will focus on four local concepts, namely Noctimik, Natoho aski, Atoske aski and Nitaskinan, each revealing an aspect of their territoriality in the contemporary context.